Attributes of Drying Define the Structure and Functioning of Microbial Communities in Temperate Riverbed Sediment - Schreckinger, José; Mutz, Michael; Mendoza-Lera, Clara; Frossard, Aline (Frontiers in Microbiology, 2021)
Combined effects of climate change and increasing anthropogenic water demand have increased and extended dry period occurrences in rivers worldwide. Riverbed drying can significantly affect sediment microorganisms, crucial drivers of biogeochemical processes in lotic systems. In this study, we evaluated how sediment bacterial and fungal community structure and composition (based on 16S rRNA gene and ITS metabarcoding) and microbial functions (community respiration and extracellular enzymatic activities) respond to different riverbed drying intensities over 90 days. Riverbed sediment collected in a flowing reach of the Spree river in northeastern Germany was dried under different rates in outdoor mesocosms during the summer months of 2018. Our results demonstrate that drying attributes (duration and intensity) and sediment organic matter (OM) content play a crucial role in sediment microbial community assembly and functioning throughout drying. Milder drying surprisingly triggered a more rapid and drastic change in the microbial community composition and diversity. After 90 days of drying, Bacilli (Firmicutes) became the dominant bacterial class in most treatments, except in sediments with low OM content under the most severe drying treatment. Fungal amplicon sequence variants (ASVs) from Dothideomycetes (Ascomycota) had by far the highest relative abundance in all our treatments at the end of the drying experiment, making up 65.1% to 94.0% of the fungal reads. CO2 fluxes, a proxy for sediment community respiration, were rapidly and strongly affected by drying in all treatments. Our results imply that even short riverbed drying periods are likely to have significant consequences for the biogeochemical dynamics in recently formed non-perennial temperate rivers.